Characteristics of high-quality early childhood education and care: a study from Australia - Phillips, Alicia; Boyd, Wendy (Frontiers in Education, 2023)
The early childhood environment influences a young child's growth, wellbeing, and development, and the young child's environment determines lifelong outcomes. The impact of the environment on children's developing brain capacity has been shown to affect the hard wiring that occurs in the 1st years of life. Brain development in the early years is shaped and formed in response to environmental experiences. The learning environment in early childhood education and care (ECEC) services is designed by the early childhood educators—for example, by establishing and implementing routines, deciding on how to resource the environment, and developing and maintaining relationships with children, families, and staff. The Australian Children's Education and Care Quality Authority (ACECQA) has developed and implemented a national quality standard (NQS) that addresses the quality of the learning environment in ECEC services. The NQS comprises seven quality areas that early childhood educators implement. Even though early childhood educators are the key decision-makers in implementing quality learning experience for children, their perspectives on the NQS have not been heard. This study presents the early childhood educators' perspectives on the characteristics of long day care (LDC) centers (for children aged from birth to 5 years) that they perceived to be important for provision of high-quality ECEC. Findings are presented from 15 interviews with early childhood educators regarding their perspectives of what characteristics enabled their LDC center to be assessed as Exceeding the NQS, one of the highest quality ratings possible. Findings indicate that the educator characteristics and their qualities in leadership and teamwork were important in determining high-quality ECEC. However, while the educators' attributes were deemed important, it was clear that there was an interconnectedness of factors including the relationships between children, families, and educators, the financial capacity, the governance, and structure of the LDC center that contributed to the provision of high-quality ECEC. Recommendations are that LDC centers could be incentivised to provide professional learning for staff leadership, teamwork, and capability to provide high-quality ECEC.